Ciências sociais e intelectualidade: Ciência, educação e politica - de Moraes, Lívia Bocalon Pires [UNESP] (FapUNIFESP (SciELO), 2016)
The article intends to understand the relations between social sciences, sociological analysis and the planning of public school education in Brazil, especially regarding the actions of some social scientists - Fernando de Azevedo, Anísio Teixeira, Florestan Fernandes, and Darcy Ribeiro -, aiming to constitute and modernize the country through the rational intervention of the intelligentsia in the state level. To do so, it discusses the notion of intellectual and the actions of part of this social group in Brazil, at different historical moments, highlighting the social function they attributed to themselves in each context and the primacy they gave to formal education as a possibility of constitution of a new country. It highlights the actions of Anísio Teixeira and Fernando de Azevedo, their conceptions of sociology and education, their involvement with Escola Nova movement and with educational legislation, and their influence on the thought and intellectual and political work of Florestan Fernandes and Darcy Ribeiro. It discusses the two authors' understanding of the social function of intellectuals and sociology, their engagement in public education by means of movements such as the Campaign in Defense of Public School, public positions in the educational area and political party work, and points out similarities, such as the defense of compulsory, public, secular, free school, given the diversity of projects and points of view of each one of them. Finally, it discusses the recent institutional context of social sciences in Brazil and the limits and possibilities that this condition offers to their involvement with the educational issue.
Social sciences and intelligentsia: Science, education and politics
Keywords: Anísio teixeira; Darcy ribeiro; Fernando de azevedo; Florestan fernandes; Public school education